Growth, survival and the histology of the digestive tract of juvenile Osteoglossum bicirrhosum (Cuvier, 1829) fed three diets containing different protein and lipid levels. (December 2015) - Darias, M. J.; Gómez, M. A.; Tello, S.; Gisbert, E.
Summary: The influence of three commercial diets with different protein and lipid contents (40 : 14, 45 : 8, 48 : 8 protein : lipid – P : L, in % dry weight of diet) on growth performance, survival and the histology of the liver and intestine was analysed in early juveniles of silver arowana, Osteoglossum bicirrhosum, reared in captivity. Individuals (initial wet weight– W i = 1.07 ± 0.04 g; total length–TL = 6.0 ± 0.17 cm) were raised in triplicate (n = 12 fish per tank) at 26.2 ± 0.1°C and fed one of three commercial diets over 60 days. At the end of the trial, survival (90.5 ± 3.3%) and condition factor (0.5 ± 0.02) were not affected by dietary treatments, whereas specific growth rate, TL and W gain were lower in animals fed the 40P : 14L diet. Histological analysis revealed a larger accumulation of lipid droplets in the intestines of the group supplied with the 40P : 14L diet, as well as a larger surface of hepatic lipid vacuoles compared to the other treatments, although no signs of steatosis were observed. Juveniles fed the 48P : 8L diet displayed the lowest liver lipid accumulation; however, a protein content higher than 45% did not improve growth performance. The intestine and liver lipid accumulation of individuals fed the 45P : 8L diet might indicate a more balanced lipidic metabolism. Intestine and liver histologies proved to be useful markers to identify the nutritional condition in juveniles of O. bicirrhosum, even when differences in nutritional composition were subtle (i.e. protein variation of 3%).